Diagnostic Accuracy of High Resolution Computed Tomography Chest in Active Pulmonary Tuberculosis (Nepalese Journal of Radiology, 2025)
Introduction: Pulmonary Tuberculosis is a common health problem in our country. It is one of the top 10 causes of death in Nepal. The diagnostic guidelines are primarily based on Acid Fast Baccili (AFB) smear on sputum and Gene Xpert test. The objective of this study is to determine the diagnostic accuracy of HRCT chest in pulmonary tuberculosis.Methods: This was a retrospective study conducted in Patan Hospital from January 2020 to December 2024who underwent HRCT chest in the radiology department for suspected tuberculosis and its findings were correlated with AFB smear and Gene Xpert test.Results: A Total of 486 cases underwent HRCT chest for suspected cases of Pulmonary Tuberculosis. Diagnostic accuracy of HRCT chest in diagnosing active PTB was 69.75% with sensitivity (95.8%), specificity (54.63%), positive predictive value (55%), and negative predictive value (95.73%).Conclusions: This study concluded that HRCT chest has high diagnostic accuracy in diagnosing disease activity of pulmonary tuberculosis.